Structural Formation, Evolution, and Genetic Mechanisms of Fault in Controlling Hydrocarbon Migration of Unconventional Rocks: A Case Study of Zhuangnan Fault - Jing Wang; Yongwei Guo; Youwei Cui; Ke Sun; Huili Chu (Geofluids)
Zhuangnan fault zone was affiliated with Gubei subsag of the Zhanhua sag in Jiyang Depression, Bohai gulf basin. Zhuangnan fault zone has two functions as the main east-west strike-slip accommodation structure. That is, on the one hand, Zhuangnan fault zone inherited the rules of development of regional tectonic. On the other hand, the present structure framework of Zhanhua sag was reconstructed by Zhuangnan fault zone. In the study, there are four main seismic reflectors: T0, T1, T2, and T6. They are the basis for researching the planar and vertical features of Zhuangnan fault zone. The structural formation, evolution, and genetic mechanisms of Zhuangnan fault zone are studied from three aspects of geometry, kinematics, and dynamics. In geometry, by the closure interpretation of 43 south-north interpretation sections and 24 east-west interpretation sections, the result indicates that Zhuangnan fault zone has its special regularity and characteristic which has three-piece planar characterization (eastern part, middle part, and western part). Three types of plane combination forms are determined: arched, linear, and “S” curved type. The plane combination structure styles of the Zhuangnan fault zone mainly include feather row, horsetail, grid, diagonal, and parallel style. These planar structural features play an important role in indicating the fault zoning of Zhuangnan fault zone. Based on the plane and section structural styles of Zhuangnan fault zone and the analysis of dynamic evolution, it is found that Zhuangnan fault zone has a succession relationship between deep and shallow fault systems. From tectonic evolution and regional dynamic point of view, this paper discusses the activity law of the Zhuangnan fault zone and the boundary faults on the east and west sides of Jiyang Depression, which are Changdi fault, Wuhaozhuang fault, and Chengnan fault, respectively. This study provides a new and more reasonable explanation for the unique structural characteristics of Zhuangnan fault zone and further confirms the important role and regulation mechanism of Zhuangnan fault zone.